Konformitas dan Sifat Mencari Sensasi dengan Disiplin Berlalu Lintas - Dewi Rofiah; Aris Setiawan (Ilmu Psikologi Universitas Yudharta Pasuruan, 2020)
Teenagers can be called a transition period which is synonymous with freedom of identity. Conformity is very high at this age, as the phenomenon of illegal motor racing groups often violates traffic norms and is undisciplined with Law Number 22 Year 2009. The purpose of this study was to determine the relationship between conformity, sensation seeking nature and traffic discipline in a group of teenage illegal motor racing in Purwosari District, Pasuruan Regency. The population in this study is a group of illegal motor racing in Pasuruan. While the sample used was 112 male teenagers in the wild racing motorbike group taken with cluster sampling technique. Data collection uses a scale of conformity, with a validity coefficient between 0.373 to 0.75 and an reliability coefficient of rxx 'of 0.841. The scale of sensation seeking properties with a validity coefficient of 0.318 to 0.521, the reliability coefficient rxx ’of 0.802. While the scale of the discipline of validity across the range of validity ranges from 0.331 to 0.597 and the reliability coefficient rxx 'of 0.827. The results showed that the hypothesis stating there was a relationship between conformity, sensation seeking characteristics with traffic discipline was accepted with a correlation of Ry (1.2) of 0.38> r table 1% = 0.256, and Freg of 9.19%> of F table 1% = 4.61.